2022
DOI: 10.1146/annurev-soc-030320-031757
|View full text |Cite
|
Sign up to set email alerts
|

Deaths of Despair in Comparative Perspective

Abstract: A socially patterned epidemic of deaths of despair is a signal feature of American society in the twenty-first century, involving rising mortality from substance use disorders and self-harm at the bottom of the class structure. In the present review, we compare this population health crisis to that which ravaged Eastern Europe at the tail end of the previous century. We chart their common upstream causes: violent social dislocations wrought by rapid economic change and attendant public policies. By reviewing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 109 publications
0
23
0
Order By: Relevance
“…The biases in Western cultures may not be universal. Studies with Chinese participants do not demonstrate negative collective future biases using fluency measures (Deng et al, 2022;Mert et al, 2022), which may better align with China's trend of a continual decrease in suicide rate and increase in other quality of life measures and life expectancy (Ilic & Ilic, 2022;King et al, 2022;Zhang et al, 2022). These real-world national trends are undoubtedly complex and the result of many different factors; however, the dissociation in emotional valence for how one feels about their country's future may be somewhat reflective of or influenced by those large-scale phenomena.…”
Section: Measuring Personal and Collective Pasts And Futuresmentioning
confidence: 93%
“…The biases in Western cultures may not be universal. Studies with Chinese participants do not demonstrate negative collective future biases using fluency measures (Deng et al, 2022;Mert et al, 2022), which may better align with China's trend of a continual decrease in suicide rate and increase in other quality of life measures and life expectancy (Ilic & Ilic, 2022;King et al, 2022;Zhang et al, 2022). These real-world national trends are undoubtedly complex and the result of many different factors; however, the dissociation in emotional valence for how one feels about their country's future may be somewhat reflective of or influenced by those large-scale phenomena.…”
Section: Measuring Personal and Collective Pasts And Futuresmentioning
confidence: 93%
“…Both tables are redrawn from Case and Deaton (2017) and reprinted, with modifications, from Sterling (2020) volatility, political instability, and rising psychosocial stress. In the 1990s, after the fall of the Soviet Union and the rapid neoliberal reordering of the country's economy, Russia experienced 7.3 million excess deaths and an unprecedented fall of six years in mean life expectancy, with the largest contributions from rising levels of suicide, alcohol, and illicit drug consumption (King, Scheiring, and Nosrati 2022). In the US, the worsening domestic crisis has only been further exacerbated by the socioeconomic shockwaves of the COVID-19 pandemic.…”
Section: Daniel R Georgementioning
confidence: 99%
“…This was an opportunity for sociologists to engage publicly: bridging the academic gap with public facing work that should have illuminated the despair Trump was giving voice to. Sociologists have shown that Trump's portrayal of parts of the country has been living in an American nightmare: from deaths of despair (Case and Deaton 2021), loss of manufacturing (Mutz 2021)-irrespective of whether it is through globalization or automation, the job loss is the same, rural population decline (Berlet and Sunshine 2019;Edelman 2019;Lichter and Brown 2011), the opioid epidemic (King et al 2022): all these factors reveal parts of America that Trump's American Carnage speech described. The demographic separation that is driving college educated and those without a college education further apart has broad implications for society given that less than 40% of Americans earn a college education (Statista 2022) and data about these emerging segments of American society are ripe for exploitation by data profiteers.…”
Section: American Carnage: Mobilizing the Left Behindmentioning
confidence: 99%